Desenvolvimento e aplicação do Elisa indireto com a nucleoproteína recombinante (NPR) do vírus da doença de Newcastle - Silva, Ketherson Rodrigues [UNESP] (2015)
Newcastle disease virus (NDV) causes one of the most important infectious diseases for chickens, due to the high negative impacts for health and the demands of trade barriers to poultry industry. This requires the constant development of increasingly more effective diagnostic techniques. In this context, the nucleoprotein (NP) of VDN is one of the ideal antigenic components for immunodiagnostics, because it is more conserved and has a high immunogenicity, so that NP may improve the performance of serodiagnosis of NDV. Thus, this study aimed to determine the production profiles of anti-NDV antibodies of IgA, IgM and IgG isotypes, using recombinant NP (rNP) of VDN as a target antigen. Serum and tear samples were collected from commercial poultry flocks, and from SPF birds experimentally infected with the LaSota vaccine strain of NDV. The indirect ELISA method using the NPr VDN as coating antigen was standardized and used for the detection of anti-NDV chicken antibody isotypes IgG, IgM in serum samples and antibodies of both isotypes added of IgA isotype for lacrimal secretion samples. This ELISA method with NPr was effectively able to differentiate NDV-positive and NDV-negative serum and tear samples, and in the birds subjected to a experimental infection with vaccine strain, the seroconversion was detected earlier for the antibodies of the IgA (tear) and IgM (tear and serum) isotypes, which have reached maximum concentration on the 7th day post-infection (pi), while the IgG anti-NDV antibody levels began to be detected later and peaked at 14 days pi. Moreover, the application of ELISA in serum and lachrymal samples collected from commercial layer chickens,with the detection of two (IgG and IgM for serum samples) or three isotypes (IgG, IgM and IgA for lachrymal samples) of anti-NDV antibodies, resulted in the highest detection frequencies than each antibody isotype was individually detected. By comparing the results of serum samples for ...